Bad Ideas About Writing - Ball, Cheryl E; Loewe, Drew M (Open textbook library., 2017)
We intend this work to be less a bestiary of bad ideas about writing than an effort to name bad ideas and suggest better ones. Some of those bad ideas are quite old, such as the archetype of the inspired genius author, the five-paragraph essay, or the abuse of adjunct writing teachers. Others are much newer, such as computerized essay scoring or gamification. Some ideas, such as the supposed demise of literacy brought on by texting, are newer bad ideas but are really instances of older bad ideas about literacy always being in a cycle of decline. Yet the same core questions such as what is good writing, what makes a good writer, how should writing be assessed, and the like persist across contexts, technologies, and eras. The project has its genesis in frustration, but what emerges is hope: hope for leaving aside bad ideas and thinking about writing in more productive, inclusive, and useful ways.